Cell-Wall Changes and Cell Tension in Response to Cold Acclimation and Exogenous Abscisic Acid in Leaves and Cell Cultures. - Rajashekar, C. B. (1996)
Freeze-induced cell tensions were determined by cell water relations in leaves of broadleaf evergreen species and cell cultures of grapes (Vitis spp.) and apple (Malus domestica). Cell tensions increased in response to cold acclimation in leaves of broadleaf evergreen species during extracellular freezing, indicating a higher resistance to cell volume changes during freezing in cold-hardened leaves than in unhardened leaves. Unhardened leaves, typically, did not develop tension greater than 3.67 MPa, whereas cold-hardened leaves attained tensions up to 12 MPa. With further freezing there was a rapid decline and a loss of tension in unhardened leaves of all the broadleaf evergreen species studied. Also, similar results were observed in cold-hardened leaves of all of the species except in those of inkberry (Ilex glabra) and Euonymus fortunei, in which negative pressures persisted below -40[deg]C. Abscisic acid treatment of inkberry and Euonymus kiautschovica resulted in increases in freeze-induced tensions in leaves, suggesting that both cold acclimation and abscisic acid have similar effects on freezing behavior[mdash] specifically on the ability of cell walls to undergo deformation. Decreases in peak tensions were generally associated with lethal freezing injury and may suggest cavitation of cellular water. However, in suspension-cultured cells of grapes and apple, no cell tension was observed during freezing. Cold acclimation of these cells resulted in an increase in the cell-wall strength and a decrease in the limiting cell-wall pore size from 35 to 22 A in grape cells and from 29 to 22 A in apple cells.